\[ \quad \text { Solve the equation. } \] \[ x^{4}-4 x^{2}-60=0 \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve the equation \( x^{4} - 4x^{2} - 60 = 0 \), we can use a substitution. Let \( y = x^{2} \). Then, the equation becomes: \[ y^{2} - 4y - 60 = 0. \] Now, we can factor or use the quadratic formula. In this case, we will use the quadratic formula: \[ y = \frac{-b \pm \sqrt{b^{2} - 4ac}}{2a}, \] where \( a = 1, b = -4, c = -60 \). Plugging in these values gives us: \[ y = \frac{4 \pm \sqrt{(-4)^{2} - 4(1)(-60)}}{2(1)} = \frac{4 \pm \sqrt{16 + 240}}{2} = \frac{4 \pm \sqrt{256}}{2} = \frac{4 \pm 16}{2}. \] This results in two possible values for \( y \): 1. \( y = \frac{20}{2} = 10 \) 2. \( y = \frac{-12}{2} = -6 \) Since \( y = x^{2} \) and \( y \) cannot be negative, we only consider \( y = 10 \). Now, we revert back to \( x \): \[ x^{2} = 10, \] which gives us: \[ x = \pm \sqrt{10}. \] Thus, the solutions to the equation \( x^{4} - 4x^{2} - 60 = 0 \) are: \[ x = \sqrt{10} \quad \text{and} \quad x = -\sqrt{10}. \]